Characterizing the biofilm stoichiometry and kinetics on the media in situ based on pulse-flow respirometer coupling with a new breathing reactor. (August 2020) - Lu, Zichuan; Li, Deyong; Jiang, Lugao; Chen, Gaofeng; Li, Kaibin; Liu, Guoqiang
Abstract: Biofilm based systems and the hybrid between activated sludge and biofilms have been popularly applied for wastewater treatment. Unlike the suspended biomass, the biofilm concentration and kinetics on the media cannot be easily measured. In this study, a novel and easy-to-use approach has been developed based on pulse-flow respirometer to characterize the biofilm stoichiometry and kinetics in situ. With the new designed breathing reactor, the mutual interference between the magnetic stirring and biofilm media that happened in the conventional breathing reactor was solved. Moreover, Microsoft Excel based programs had been developed to fit the oxygen uptake rate curves with dynamic nonlinear regression. With this new approach, the yield coefficient, maximum oxidation capacity, and half-saturation constant of substrate for the heterotrophic biofilms in a fix bed reactor were determined to be 0.46 g-VSS/g-COD, 67.0 mg-COD/(h·L-media), and 4.4 mg-COD/L, respectively. Those parameters for biofilm ammonia oxidizers from a moving bed biofilm reactor were determined to be 0.17 g-VSS/g-N, 18.6 mg-N/(h·L-media), and 1.2 mg-N/L, respectively, and they were 0.11 g-VSS/g-N, 20.9 mg-N/(h·L-media), and 0.98 mg-N/L for nitrite oxidizers in the same biofilms. This study also found that the maximum specific substrate utilization rate for detached biofilms increased by 3.2 times, indicating that maintaining biofilm integrity was very important in the kinetic tests. Using this approach, the biofilm kinetics on the media can be regularly measured for treatment optimization. Graphical abstract: Image 10245 Highlights: A new respirometric method is developed for determining biofilm kinetics in situ. Excel based programs are created to fit OUR with dynamic nonlinear regression. Biofilm stoichiometry and kinetics on COD oxidation & nitrification are determined. Maintaining biofilm integrity is very important in the biofilm kinetic tests.